2016
DOI: 10.21873/anticanres.11249
|View full text |Cite
|
Sign up to set email alerts
|

Bone-targeted Novel Cytotoxic Polybisphosphonate Conjugate in Castration-resistant Prostate Cancer: A Multicenter Phase 1 Study

Abstract: Abstract. Background: Osteodex (ODX) is a cytotoxic bone-targeting polybisphosphonate, intended for treatment of bone metastasis from castration-resistant prostate cancer (CRPC). The primary objective of this study was to describe the tolerability and toxicity of such treatment by defining its maximum tolerated dose (MTD) and dose-limiting toxicity (DLT). Patients and Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…In vitro studies demonstrated that ODX had similar potency to inhibit bone resorption as zoledronate, but it also killed PC3 cells, a cell line established in 1979 from a bone metastasis of a 62-year-old Caucasian male with grade IV prostate cancer, with 10-fold higher potency than zoledronate (IC50 2 μm vs. 25 μm) [53]. DexTech completed a Phase 1 open-label, multiple ascending dose, multicenter clinical trial of ODX (ClinicalTrials.gov NCT02825628) and reported the results in 2016 [54]. Twenty-eight patients with castration-resistant prostate cancer and confirmed bone metastases were given 7 intravenous infusions of ODX every third week.…”
Section: Osteodex (Odx)mentioning
confidence: 99%
“…In vitro studies demonstrated that ODX had similar potency to inhibit bone resorption as zoledronate, but it also killed PC3 cells, a cell line established in 1979 from a bone metastasis of a 62-year-old Caucasian male with grade IV prostate cancer, with 10-fold higher potency than zoledronate (IC50 2 μm vs. 25 μm) [53]. DexTech completed a Phase 1 open-label, multiple ascending dose, multicenter clinical trial of ODX (ClinicalTrials.gov NCT02825628) and reported the results in 2016 [54]. Twenty-eight patients with castration-resistant prostate cancer and confirmed bone metastases were given 7 intravenous infusions of ODX every third week.…”
Section: Osteodex (Odx)mentioning
confidence: 99%
“…OsteoDex is a bi-functional macromolecular polybisphosphonate has osteoclast inhibitory function with anti-tumor ability [107,108]. A phase I safety study were performed in castration-resistant prostate cancer patients revealed no serious adverse effects, including renal toxicity [107]. Currently, a phase II trial testing the effect of osteodex on skeletal related pain in prostate cancer patients with bone metastases is underway (ClinicalTrias.gov: NCT02825628).…”
Section: Treatment Strategies For Men With Bone Metastasesmentioning
confidence: 99%
“…Additionally, another potential bone-targeting reagent, OsteoDex has been recently developed. OsteoDex is a bi-functional macromolecular polybisphosphonate has osteoclast inhibitory function with anti-tumor ability [107,108]. A phase I safety study were performed in castration-resistant prostate cancer patients revealed no serious adverse effects, including renal toxicity [107].…”
Section: Treatment Strategies For Men With Bone Metastasesmentioning
confidence: 99%
“…4) Although docetaxel provides a modest (2.4-month) increase in median overall survival, many patients with CRPC cannot tolerate this cytotoxic chemotherapy due to advanced age, medical comorbidities, or limited bone marrow reserves. 5) Therefore, the identification of an effective alternative therapy with less toxicity may lead to increased survival and an improved QOL.…”
mentioning
confidence: 99%